THE STEREOCHEMISTRY OF THE O(1D)+N2O-]NO+NO REACTION VIA VELOCITY-ALIGNED PHOTOFRAGMENT DYNAMICS - Brouard, M; Duxon, S; Enriquez, P; Simons, J (1992)
Velocity-aligned, superthermal O(1D) atoms generated via the photodissociation of N2O have been employed to investigate the stereodynamics of the title reaction. The power of this experimental technique, when coupled with Doppler-resolved, polarized laser-induced fluorescence probing of the reaction products, is demonstrated by reference to the specific reaction channel leading to NO(v′=0)+NO(v′=16,17), which is shown to proceed via direct stripping dynamics. Furthermore, the observed product-state selective linear and angular momenta disposals imply that the reaction is stereodynamically constrained to occur via collinear collision geometries. © 1992 American Institute of Physics.